ICT integration in teaching practice: can we go beyond the experimentation? - Marco Perini; Giuseppe Tacconi (Firenze University Press, 2017)
This study aims to analyze the experiences and the voices of the actors involved in the pilot project iCnos in order to achieve a better understanding of the ongoing process of change and to provide transferable and reusable information. This project, promoted and led by the national board of CNOS-FAP Federation, aims at introducing ICTs as support to teachers' activities and students' learning processes. Four of the VET centers involved in the project participated in this research. The qualitative analysis of data which were gathered through interviews shows that the innovation process has been taking different forms in each VET center. There are also common features in the transition from an experimental phase to implementation.   L'integrazione delle ICT nelle pratiche didattiche: è possibile andare oltre la sperimentazione? Il presente contributo si propone di analizzare e restituire le esperienze degli attori coinvolti nel progetto pilota iCnos, al fine di ottenere una migliore comprensione del processo di cambiamento in corso che fornisca informazioni trasferibili e riutilizzabili in altri contesti. Il progetto iCnos, promosso e guidato dalla direzione nazionale della federazione CNOS-FAP, mira a introdurre le Information and Communication Technologies (ICT) come supporto alle attività didattiche dei docenti e ai processi di apprendimento degli studenti dei Centri di Formazione Professionale (CFP) aderenti. Lo studio ha coinvolto quattro CFP. L'analisi qualitativa dei dati raccolti attraverso interviste ha mostrato che il processo di innovazione ha assunto forme diverse in ogni CFP ma ha consentito anche di cogliere le caratteristiche comuni del passaggio da una fase sperimentale a una fase di consolidamento dei processi innovativi.